2005
DOI: 10.17221/4176-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic growth models for cattle

Abstract: There are several ways of generalizing classical growth models to describe the complex nature of animal growth. One possibility is to construct a model based on a sum of several classical growth functions. In this paper, such multiphasic growth models for breeding bulls of the Czech Pied cattle based on the sum of two logistic functions are studied. The logistic function was chosen as a base for the models due to the relatively low degree of nonlinearity for the growth data. The paper describes three steps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
(6 reference statements)
1
14
0
Order By: Relevance
“…Several studies have reported significant correlations between estimates of growth curve parameters and reproductive traits in cattle (Beltrán et al, 1992;Menchaca et al, 1996;Bayram et al, 2004;Nesetrilova, 2005). Results indicated a negative association between the maturing rate index and the young cow reproductive traits age at first calving and calving interval, suggesting that early-maturing cows were younger at first calving and had shorter calving intervals, both indicators of improved fertility.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported significant correlations between estimates of growth curve parameters and reproductive traits in cattle (Beltrán et al, 1992;Menchaca et al, 1996;Bayram et al, 2004;Nesetrilova, 2005). Results indicated a negative association between the maturing rate index and the young cow reproductive traits age at first calving and calving interval, suggesting that early-maturing cows were younger at first calving and had shorter calving intervals, both indicators of improved fertility.…”
Section: Discussionmentioning
confidence: 98%
“…The most commonly used analytical method for evaluation is the multi-trait animal model, the traits being net gain (calculated as carcass weight divided by age), "SEUROP" carcass conformation score (grades S to P according to muscularity), fatness classes (1 -lean, 5 -very fat) and meat percentage (Schild et al 2003). Nesetrilova (2005) described the growth curve for the Czech Fleckvieh cattle up to 1,400 days of age using a multiphase growth model. Vesela et al (2011) estimated the genetic indices of beef cattle production traits in the SEUROP system.…”
Section: Cattlementioning
confidence: 99%
“…Non-linear growth functions (e.g., Bhowmick & Bhattacharya, Gompertz, Logistic, Von Bertalanffy, Weibull and Richards), with parameters estimated by regression, describe animal growth (Bhowmick and Bhattacharya, 2014;Chizzotti et al, 2008;Forni et al, 2009;Freetly et al, 2011;Marinho et al, 2013;Nesetrilová, 2005). However, they have limited capacity to estimate body composition (i.e., fat and protein), thus, neglecting the possible interactions between metabolism and composition of gain dynamics (NRC, 1996).…”
Section: Introductionmentioning
confidence: 99%